TI_GERICHTE 32.2017.44 vom 15. Februar 2017 , Rendita rifiutata in assenza di un grado di invalidità sufficiente. TCA conferma - TI Tribunale d'appello (2017)
Rendita rifiutata in assenza di un grado di invalidità sufficiente. TCA conferma